Single-Arm Phases 1 and 2 Trial of Niraparib in Combination With Pembrolizumab in Patients With Recurrent Platinum-Resistant Ovarian Carcinoma - Konstantinopoulos, Panagiotis A; Waggoner, Steven; Vidal, Gregory A; Mita, Monica; Moroney, John W; Holloway, Robert; Van Le, Linda; Sachdev, Jasgit C; Chapman-Davis, Eloise; Colon-Otero, Gerardo; Penson, Richard T; Matulonis, Ursula A; et al. (JAMA oncology, 2019)
Patients with recurrent ovarian carcinoma frequently develop resistance to platinum-based chemotherapy, at which time treatment options become limited. To evaluate the poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitor niraparib combined with pembrolizumab in patients with recurrent ovarian carcinoma. The TOPACIO/KEYNOTE-162 (Niraparib in Combination With Pembrolizumab in Patients With Triple-Negative Breast Cancer or Ovarian Cancer) trial, an open-label, single-arm phases 1 and 2 study enrolled women with advanced or metastatic triple-negative breast cancer (TNBC) or recurrent ovarian carcinoma, irrespective of BRCA mutation status. Median follow-up was 12.4 months (range, 1.2 to ≥23.0 months). Data were collected from April 15, 2016, through September 4, 2018, with September 4, 2018, as a data cutoff, and analyzed from September 4, 2018, through January 30, 2019. The recommended phase 2 dose (RP2D) was 200 mg of oral niraparib once daily and 200 mg of intravenous pembrolizumab on day 1 of each 21-day cycle. The primary objectives of phase 1 were to evaluate dose-limiting toxic effects and establish the RP2D and dosing schedule. The primary objective of phase 2 was to assess objective response rate (ORR; complete plus partial responses). Results from the phase 1 ovarian carcinoma and TNBC cohorts and phase 2 ovarian carcinoma cohort are reported. Because of the similarity in the phase 1 and 2 ovarian carcinoma populations, the data were pooled to perform an integrated efficacy analysis. Fourteen patients (9 with ovarian carcinoma and 5 with TNBC) in phase 1 and 53 patients with ovarian carcinoma in phase 2 were enrolled, for a pooled ovarian carcinoma cohort of 62 patients (median age, 60 years [range, 46-83 years]). In the integrated efficacy phases 1 and 2 ovarian carcinoma population (60 of 62 evaluable patients), ORR was 18% (90% CI, 11%-29%), with a disease control rate of 65% (90% CI, 54%-75%), including 3 (5%) with confirmed complete responses, 8 (13%) with confirmed partial responses, 28 (47%) with stable disease, and 20 (33%) with progressive disease. The ORRs were consistent across subgroups based on platinum-based chemotherapy sensitivity, previous bevacizumab treatment, or tumor BRCA or homologous recombination deficiency (HRD) biomarker status. Median duration of response was not reached (range, 4.2 to ≥14.5 months). At data cutoff, 2 patients with a response and 1 patient with stable disease continued to receive treatment. Niraparib in combination with pembrolizumab is tolerable, with promising antitumor activity for patients with ovarian carcinoma who have limited treatment options regardless of platinum status, biomarker status, or prior treatment with bevacizumab. Responses in patients without tumor BRCA mutations or non-HRD cancers were higher than expected with either agent as monotherapy. ClinicalTrials.gov identifier: NCT02657889.